Colorectal anastomosis dehiscence following radical surgical operation for rectal carcinoma - Trifunović Bratislav; Delić Jovan; Mirković Darko; Jovanović Milan; Kršić Jovan; Zarić Zoran (Vojnosanitetski Pregled)
Background/Aim. Colorectal cancer (CRC) is one of the biggest health problems of modern humanity, especially in highly developed countries. In Serbia about 3,200 patients suffer from CRC, out of whom about 1,100 patients suffer from rectal cancer (RC), while about 2,100 patients suffer from other colon segments cancer. The aim of the study was to show the incidence genesis of one of the possible early postoperative complications regarding dehiscence of the colorectal anastomosis (CRA) with a group of patients suffering from RC and operated by using sphincter-saving procedures, in the period from 1993 to 2007, and then to compare the incidence genesis of these complications with those in the published series of the reporting colorectal institutions. Methods. The research included 242 patients radically operated on for RC in a 15-year period using some of sphincter-saving procedures following by a careful analysis of the symptoms of subclinical dehyscencias not solved with the reintervention as well as of the clinically evidented dehyscencias mostly solved by reoperation. Results. With 22 (9.1%) patients in the first 10 postoperative days there were early postoperative symptoms of CRA dehiscence. In 6 (2.47%) of the patients there were subclinical signs of raised body temperature, less quantity of feces content, and after the conservative treatment they ended in spontaneous process of rehabilitation. In 16 (6.61%) patients there was clinically evidented anastomosis dehiscence followed by abundant drainage of feces content, signs of local peritonitis, pelvic sepsis, so we had to undertake surgical intervention. Conclusion. Comparing the results of a few tenths of published studies with our results we proved that performing and operative technique of colorectal anastomosis in the patients suffered and radically surgically treated for RC, is quite adequate with the operative technique in reporting world institutions that are engaged in surgical treatment of RC.